1992
DOI: 10.1161/01.atv.12.5.584
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of heterozygous familial hypercholesterolemia. DNA analysis complements clinical examination and analysis of serum lipid levels.

Abstract: The concordance of clinical and molecular genetic diagnoses of heterozygous familial hypercholesterolemia (FH) was studied in 65 subjects (10 propositi and 55 first-degree relatives) from 10 families with FH. Nine propositi were carriers of the FH-Helsinki deletion of the low density lipoprotein (LDL) receptor gene, prevalent in the Finnish population, while a new deletion, extending from intron 14 to intron 15 of the LDL receptor gene, was identified in one family. Serum LDL cholesterol levels used in the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 29 publications
1
33
1
Order By: Relevance
“…810 There appear to be no differences in serum lipid levels between patients with these two mutation types. 9 In our recent study 10 on the concordance of clinical and molecular genetic diagnosis of FH we encountered another LDL receptor gene mutation, designated FHEspoo. Preliminary data suggested that the FH-Espoo gene most likely results from deletion of exon 15 of the LDL receptor gene.…”
Section: F Amilial Hypercholesterolemia (Fh) Is Character-mentioning
confidence: 99%
See 2 more Smart Citations
“…810 There appear to be no differences in serum lipid levels between patients with these two mutation types. 9 In our recent study 10 on the concordance of clinical and molecular genetic diagnosis of FH we encountered another LDL receptor gene mutation, designated FHEspoo. Preliminary data suggested that the FH-Espoo gene most likely results from deletion of exon 15 of the LDL receptor gene.…”
Section: F Amilial Hypercholesterolemia (Fh) Is Character-mentioning
confidence: 99%
“…Preliminary data suggested that the FH-Espoo gene most likely results from deletion of exon 15 of the LDL receptor gene. 10 Exon 15 is of special interest in that it encodes the domain with O-linked sugars situated extracellularly between the membrane-spanning region and the epidermal growth factor homology domain of the LDL receptor protein. 1112 Davis et al 13 used oligonucleotide-directed mutagenesis to delete the cDNA segment encoding this receptor domain with clustered serine and threonine residues.…”
Section: F Amilial Hypercholesterolemia (Fh) Is Character-mentioning
confidence: 99%
See 1 more Smart Citation
“…A DNA vs cholesterol diagnostic study of an extended Irish family showed that 15 ± 20% of family members would have been incorrectly diagnosed based on cholesterol testing alone, 24 and in a Finnish study, 10 ± 20% of relatives would have been misdiagnosed. 21 Month-tomonth variability of lipids and lipoproteins and apolipoproteins has also been observed, and in a study of 63 school children, recent infection significantly lowered high density lipoprotein (HDL) whilst LDL-C was shown to be slightly elevated. 25 Thus total cholesterol, LDL-C and triglyceride levels could be falsely high after an acute infection and result in misdiagnosis.…”
Section: Introductionmentioning
confidence: 96%
“…Screening is simpler in populations where there is a founder gene, such as South Africa 26 and Quebec in Canada, 27 or in populations where there are a limited number of mutations in the majority of FH individuals, such as Iceland 28 and Finland 21 or where there are good traceable family records such as Utah, USA. 29 In heterogeneous populations, a larger number of mutations are found and thus a wider screening approach must be undertaken, as reported in Denmark, 30 Netherlands 31,32 and Italy.…”
Section: Introductionmentioning
confidence: 99%